Cadmium passivation induced negative differential resistance in cove edge graphene nanoribbon device - Kharwar, Saurabh; Gity, Farzan; Hurley, Paul K.; Ansari, Lida (Scientific reports, 2025)
Graphene nanoribbons (GNRs) have emerged as promising candidates for nanoelectronic devices due to their unique electronic and transport properties. In this study, we investigate the impact of passivation on cove-edge graphene nanoribbon (CGNR) using both cadmium (Cd) and hydrogen (H) atoms. Through a comprehensive density functional theory (DFT) analysis coupled with non-equilibrium Green’s function (NEGF) simulations, we explore the electronic transport properties and device behavior of these passivated CGNRs. Our results reveal a distinctive semiconductor-to-metal transition in the electronic properties of the Cd-passivated CGNRs. This transition, induced by the interaction between Cd atoms and the GNR edges, leads to a modulation of the bandstructure and a pronounced shift in the conductance characteristics. Interestingly, the Cd-passivated CGNR devices exhibit negative differential resistance (NDR) with remarkably high peak-to-valley current ratios (PVCRs). NDR is a phenomenon critical for high-speed switching, enables efficient signal modulation, making it valuable for nanoscale transistors, memory elements, and oscillators. The highest PVCR is measured to be 53.7 for Cd-CGNR-H which is x10 and x17 times higher than strained graphene nanoribbon and silicene nanoribbon respectively. These findings suggest the promising potential of passivated CGNRs as novel components for high-performance nanoelectronic devices.